UPAYA MENINGKATKAN PRESTASI BELAJAR PKN MATERI LEMBAGA-LEMBAGA NEGARA DAN SUSUNAN PEMERINTAHAN TINGKAT PUSAT DENGAN METODE PETA KONSEP BERGAMBAR - Hartono Hartono (Program Pascasarjana Universitas Islam Darul `Ulum Lamongan, 2021)
This study aims to describe the improvement of Civics learning outcomes by using the concept map method in fourth grade students of SDN Pangkatrejo I, Sugio District, Lamongan Regency. This type of research is classroom action research. The research subjects were fourth grade students, amounting to 18 students. The method of data collection in this study used tests, observation and documentation. The research instrument was in the form of tests and observation sheets. The data analysis technique used is descriptive quantitative and qualitative. Student learning outcomes from the cycle of student achievement are still low because under the KKM the class average reaches a value of 64.4. In the first cycle after applying Civics learning using media Picture Concept Maps showed PKn learning outcomes from the average class increased to 75.0 had reached KKM but learning completeness was still 72.2% had not reached 75% then proceed to cycle II. In the second cycle the class average reached a value of 82.8. Student mastery learning has also been completed with the percentage of completeness 88.9% exceeding the minimum completeness criteria which is 75%.